PENGARUH KEMUDAHAN BERTRANSAKSI TERHADAP KEPUTUSAN MENGUNAKAN AGEN BRILINK ALFIN DESA LILIRIAWANG KECAMATAN BENGO KABUPATEN BONE - Pertiwi, Mega; Akib, Haedar; S., Muh Rizal; Niswaty, Risma; Aslinda, Andi (Humano: Jurnal Penelitian, 2023)
This research examines the influence of ease of transacting on decisions using brilink agents. The purpose of this study was to determine the level ofease of transacting with brilink agents, to find out the level the decision to use a brilink agent, and to determine the effect of usage decisions on ease of transaction on the brilink agent. This research approach is quantitative. This research was carried outin Liliriawang Village, Bengo District, Bone Regency. Sources of data in the study areAlfin's Brilink Agent Customerin November 2021. Data collection techniques are in the form of observation, questionnaires, interviews, and literature studies. Data analysis techniques in the form of normality test, descriptive analysis, simple linear regression analysis, t test, correlation coefficient analysis, and analysis of the coefficient of determination. The results of the study indicate that the indicators used in each of these variables indicate where the ease of transactions is in the very good category. The indicators on the use decision variables are in the very good category. Based on the correlation test, there is a very high relationship between the two variables. It can be concluded that there is an influence between the ease of transactions on the decision to use a brilink agent.